2021
DOI: 10.7759/cureus.13499
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Cardioembolic and Large Artery Atherosclerotic Clots Using Reverse Phase Protein Array Technology Reveals Key Cellular Interactions Within Clot Microenvironments

Abstract: Thrombus characteristics are dependent on clot composition, but identification of the etiology based on histological analysis has proved inconclusive. Identification of proteomic signatures may help to differentiate between clots of different etiologies such as cardioembolic, large artery atherosclerotic, and other known etiologies, information that could enhance an individualized medicine approach to secondary stroke prevention. In this study, total protein extracts from cardioembolic (n=25) and large artery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Proteins encoded by key DEGs identified in our study have also been found to be differentially expressed in proteomic studies of stroke thrombi 23–27. For example, protein levels of apolipoprotein E (APOE), which had increased gene expression in CE clots, were also found to be higher in CE on liquid chromatography coupled to tandem mass spectrometry analysis by Dargazanli et al 26.…”
Section: Discussionsupporting
confidence: 59%
“…Proteins encoded by key DEGs identified in our study have also been found to be differentially expressed in proteomic studies of stroke thrombi 23–27. For example, protein levels of apolipoprotein E (APOE), which had increased gene expression in CE clots, were also found to be higher in CE on liquid chromatography coupled to tandem mass spectrometry analysis by Dargazanli et al 26.…”
Section: Discussionsupporting
confidence: 59%
“…Abbasi et al recently compared 25 CE vs. 23 LAA thrombi using proteomic techniques and applying pathway analyses and reverse-phase protein arrays to assess cellular interactions within the clots [ 36 ]. The analysis revealed strong interactions between PPAR-gamma, arginase-1, CD63, CD234, PKCαβ Thr 638/641, and VWF in CE clots, indicating that platelet signaling dominates in CE vs. LAA thrombi.…”
Section: Multiomic Studiesmentioning
confidence: 99%
“…Considering the importance of thrombus composition and structure in IVT resistance, identifying factors that influence these parameters may help better predict response to IVT. The determinants are most likely multifactorial, encompassing stroke etiology (eg, cardioembolic vs large artery atherosclerosis) [ 131 , 132 ] and underlying conditions (eg, cancer) [ 133 ], risk factors, comorbidities, and inflammation, all of which factors can be interrelated. With respect to etiology, there is converging evidence that AIS thrombi from cardioembolic origin have higher leukocyte, DNA, and NET content as compared with AIS thrombi linked to large artery atherosclerosis [ 82 , 131 , 134 , 135 ].…”
Section: Potential Determinants Of Thrombus Composition and Structurementioning
confidence: 99%
“…The determinants are most likely multifactorial, encompassing stroke etiology (eg, cardioembolic vs large artery atherosclerosis) [ 131 , 132 ] and underlying conditions (eg, cancer) [ 133 ], risk factors, comorbidities, and inflammation, all of which factors can be interrelated. With respect to etiology, there is converging evidence that AIS thrombi from cardioembolic origin have higher leukocyte, DNA, and NET content as compared with AIS thrombi linked to large artery atherosclerosis [ 82 , 131 , 134 , 135 ]. Whether the higher DNA and NET content of AIS thrombi from cardioembolic origin translates into higher resistance to IVT remains to be determined.…”
Section: Potential Determinants Of Thrombus Composition and Structurementioning
confidence: 99%